Validity of Adobe After Effect Assisted Learning Media Based on Realistic Mathematics Education for Primary Schools in Medan - Landong, Ahmad; Rangkuti, Yulita Molliq (AL-ISHLAH: Jurnal Pendidikan, 2024)
Mathematics learning is made up of interconnected concepts and materials, therefore understanding the fundamentals is critical. The purpose of this study is to assess the validity of developing mathematics learning medium utilizing animated videos. Adobe After Effects (AAE) is based on Realistic Mathematics Education (RME) for elementary school students in Medan. This study and development of learning material was conducted utilizing research and development procedures (RD). The ADDIE model has been adapted, and only the analysis, design, and development phases have been carried out in this research. The data gathering approach consisted of observation, interviews, questionnaires, and documentation based on the validation results of two media experts and three teachers (material experts) from three schools. The data analysis technique employed is to convert qualitative data to quantitative data. The Material Expert validity test yielded good findings, with an average score of 3 out of a possible 4 points. The media expert validity test yielded a good standard, with a mean score of 3.20 and a maximum value of 4. It was concluded that the results of the animation video mathematics learning media validation test assisted by AAE based on RME were good for use in learning at school.